Ensayos de tensión y flexión sobre una nueva propuesta de junta en pilotes hincados (2017)
As a result of this degree work, a new type of joint for driven piles was developed, in order to study its behavior in the face of the main work demands: tension and bending. For this, four tests were carried out at simple tension and one at bending on the proposed joint model with the assembly discussed below, one for each type of test; As described in the development of this work, these tests were conducted in the Materials Laboratory of the Colombian School of Engineering Julio Garavito. Experimentally evaluating the behavior in the presence of different static stresses (bending and axial tension), under normal conditions, that is, without considering the incidence of being a buried structure. From the results of the experimental tests, the critical points and the capacity were determined before the mentioned stresses of the tested joint. The information that was tabulated was obtained, in such a way that it serves as a guide for the structural design of this type of joints. The joint prototype designed met the conditions to withstand the most critical stresses that may be subject to its useful life